The Effect Of Context On Arabic Reading Skills Among Normal And Dyslexic Students - Tachema Radia; Medouri Yamina; Bouanani Ghania (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study describes the impact of context on reading competence in elementary school students (normal and dyslexic). Through an Experiment consisting of three modes of context in which students are tested in reading competence, where the first experiment includes the absence of context, the second experiment concerns the predictive context. The third experiment Concerning the neutral context, a sample of 20 students was represented. We relied on evaluating reading competence on two indicators: reading speed, number, and types of errors. The results showed that context affects reading proficiency, and this effect was different between dyslexic students and good readers, where context (predictive and neutral) helped improve reading skills in dyslexic students through a decrease in the number of errors and the reaction time compared to the experience of the absent context. It was the opposite result for good readers. The errors appear to be different according to the three types of context. Letter or syllable withdrawal errors were the greatest in the experience of no context. Moreover, al harakat (vowels) errors were most common in the experience of context predictive and neutral context. Contextualization errors follow this—withdrawal of letters or syllables, then lexicalizations, and decoding errors.